2013
DOI: 10.1371/journal.pone.0083245
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Eating Disorder Examination Questionnaire (EDE-Q) and Norms for Rural and Urban Adolescent Males and Females in Mexico

Abstract: AimsTo contribute new evidence to the controversy about the factor structure of the Eating Disorder Examination Questionnaire (EDE-Q) and to provide, for the first time, norms based on a large adolescent Mexican community sample, regarding sex and area of residence (urban/rural). MethodsA total of 2928 schoolchildren (1544 females and 1384 males) aged 11-18 were assessed with the EDE-Q and other disordered eating questionnaire measures.ResultsConfirmatory factor analysis of the attitudinal items of the EDE-Q d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
5
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(105 citation statements)
references
References 50 publications
10
87
5
3
Order By: Relevance
“…Female adolescents in this study reported higher mean EDE-Q scores on the subscales and global scale compared to previously published studies of healthy female adolescents (Carter et al, 2001; Machado et al, 2014; Mond et al, 2014; Penelo et al, 2013). In other words, female adolescents in the present study reported greater severity of eating disorder psychopathology compared to healthy female adolescents.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Female adolescents in this study reported higher mean EDE-Q scores on the subscales and global scale compared to previously published studies of healthy female adolescents (Carter et al, 2001; Machado et al, 2014; Mond et al, 2014; Penelo et al, 2013). In other words, female adolescents in the present study reported greater severity of eating disorder psychopathology compared to healthy female adolescents.…”
Section: Discussioncontrasting
confidence: 65%
“…Normative EDE-Q data are available for healthy adolescent girls in the United Kingdom (Carter, Stewart, & Fairburn, 2001) and Portugal (Machado et al, 2014), and healthy adolescent boys and girls in Australia (Mond et al, 2014), Malaysia (Musa et al, 2016), and Mexico (Penelo, Negrete, Portell, & Raich, 2013). One Swedish study (Mantilla & Birgegard, 2016) reported norms on clinical and healthy adolescents using a 14-day time frame version of the EDE-Q, which had been specifically modified for adolescents (Carter et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, evidence of invariance across gender has been described for the two-factor model among Mexican teenagers (Penelo et al, 2013). In this regard, evidence of invariance across gender has been described for the two-factor model among Mexican teenagers (Penelo et al, 2013).…”
Section: Confirmatory Factor Analysis and Measurement Invariance Ofmentioning
confidence: 91%
“…While one study noted support for the original four-factor model among university students in Spain (Penelo, Villarroel, Portell, & Raich, 2012), another study has rejected the four-factor model among US college athletes (Darcy, Hardy, Crosby, Lock, & Peebles, 2013) and among teenagers in Mexico (Penelo, Negrete, Portell, & Raich, 2013). While one study noted support for the original four-factor model among university students in Spain (Penelo, Villarroel, Portell, & Raich, 2012), another study has rejected the four-factor model among US college athletes (Darcy, Hardy, Crosby, Lock, & Peebles, 2013) and among teenagers in Mexico (Penelo, Negrete, Portell, & Raich, 2013).…”
Section: Confirmatory Factor Analysis and Measurement Invariance Ofmentioning
confidence: 99%
“…En éste estudio se utilizó la versión adaptada y validada en población española por Peláez, Labrador & Raich (2012), con consistencia interna aceptable para las cuatro escalas (α≥.74). En población mexicana se obtuvo una consistencia interna satisfactoria (α≥.80) (Penelo, Negrete, Portell, & Raich, 2013). A mayor puntuación, mayor gravedad en la patología alimentaria.…”
Section: Instrumentosunclassified